An Interdependence Analysis of the Trade Network of Key Exporting Countries: Focusing on the Asia-Pacific Region (U.S., China, India, Japan, and South Korea) - Yazawa, Nobuo; Nam, Hee-Hyun (International Journal of Economics and Financial Issues, 2024)
This study analyzes the trade interdependence among five key Asia-Pacific exporting nations—the U.S., China, India, Japan, and South Korea—between 1992 and 2020. Utilizing network theory, we investigate the evolution of trade relations, especially in response to major global events such as economic crises and geopolitical shifts. Specifically, our analysis quantitatively identifies two distinct effects of economic crises on trade networks: the contraction effect, which results in a significant reduction in total trade volume, and the structural shift effect, characterized by changes in the configuration of the network, leading to weakened interdependence. Moreover, our findings reveal that while trade interdependence strengthened until 2011, there has been a noticeable decline since, driven by protectionist policies and regional trade realignments. Additionally, we highlight the increasing centrality of China and India in global trade networks, which is reshaping the traditional U.S.-Japan-led structure. These developments underscore the dynamic nature of global trade and its vulnerability to both structural and economic shocks. Ultimately, the results offer valuable insights for policymakers aiming to navigate the complexities of the modern global economy, emphasizing the importance of resilience in trade relations.